Quantitative Proteomic Analysis Identifies MAPK15 as a Potential Regulator of Radioresistance in Nasopharyngeal Carcinoma Cells - Li, Zhanzhan; Li, Na; Shen, Liangfang; Fu, Jun (Frontiers in Oncology, 2018)
Since resistance to radiotherapy remains refractory for the clinical management of nasopharyngeal cancer (NPC), further understanding the mechanisms of radioresistance is necessary in order to develop more effective NPC treatment and improve prognosis. In this study, an integrated quantitative proteomic approach involving tandem mass tag labeling and liquid chromatograph-mass spectrometer was used to identify proteins potentially responsible for the radioresistance of NPC. The differential radiosensitivity in NPC model cells was examined through clonogenic survival assay, CCK-8 viability assay, and BrdU incorporation analysis. Apoptosis of NPC cells after exposure to irradiation was detected using caspase-3 colorimetric assay. Intracellular reactive oxygen species (ROS) was detected by a dichlorofluorescin diacetate fluorescent probe. In total, 5,946 protein groups were identified, among which 5,185 proteins were quantified. KEGG pathway analysis and protein-protein interaction enrichment analysis revealed robust activation of multiple biological processes/pathways in radioresistant CNE2-IR cells. Knockdown of MAPK15, one up-regulated protein kinase in CNE2-IR cells, significantly impaired clonogenic survival, decreased cell viability and increased cell apoptosis following exposure to irradiation, while over-expression of MAPK15 promoted cell survival, induced radioresistance and reduced apoptosis in NPC cell lines CNE1, CNE2, and HONE1. MAPK15 might regulate radioresistance through attenuating ROS accumulation and promoting DNA damage repair after exposure to irradiation in NPC cells. Quantitative proteomic analysis revealed enormous metabolic processes/signaling networks were potentially involved in the radioresistance of NPC cells. MAPK15 might be a novel potential regulator of radioresistance in NPC cells, and targeting MAPK15 might be useful in sensitizing NPC cells to radiotherapy.